Collaborative Planning Model for Charging Station and Distribution Network Considering User Benefits. (December 2017) - Chen, Bin; Zhang, Yi; Tang, Shuoya; Xiang, Yue; Liu, Junyong; Xiong, Jun; Huang, Daoshan; Chen, Jinxiang; Liu, Zhixuan
Abstract: With the increasing of electric vehicles (EVs) users, a large amount of reserve charging infrastructure have to be deployed in distribution systems to the uncertain charging demand, which may lead to redundant investment. In order to reduce unnecessary investment and optimize the plan of charging station and distribution network, a multi-objective planning model is proposed. The objectives of planning model include the benefits of both distribution network and EV user. The proposed method has been verified on a modified 54-bus distribution and 19-node road system. The results shows that the proposed model can give collaborative plan, and ensure the benefits of both the distribution side and user side.